Back to the fifties nostalgia, Hollywood film, and popular music of the seventies and eighties - Dwyer, Michael D. (Oxford music/media series, 2015)
'Back to the Fifties' examines the explosion of Fifties nostalgia in Hollywood film and popular music from the early 1970s to the late 1980s. It both complicates and transcends standard diagnoses of the political function of nostalgia in popular media, and sheds new light on a crucial and underexamined period in American politics and culture. By closely examining the ways that 'the Fifties' were remade and recalled in films and in pop music, the book notes the importance of 'the Fifties' to a generation of Americans and explores the ways popular culture facilitates cultural memory